2016
DOI: 10.1088/0953-4075/49/8/085301
|View full text |Cite
|
Sign up to set email alerts
|

Impenetrable mass-imbalanced particles in one-dimensional harmonic traps

Abstract: Strongly interacting particles in one dimension subject to external confinement have become a topic of considerable interest due to recent experimental advances and the development of new theoretical methods to attack such systems. In the case of equal mass fermions or bosons with two or more internal degrees of freedom, one can map the problem onto the well-known Heisenberg spin models. However, many interesting physical systems contain mixtures of particles with different masses. Therefore, a generalization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 81 publications
0
42
0
Order By: Relevance
“…In particular, there has been a remarkable increase of interest in exploring properties of various quantum composite systems [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In recent years, both the entanglement and Shannon Entropy in helium and helium-like ions have also accelerated a great research attention [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there has been a remarkable increase of interest in exploring properties of various quantum composite systems [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In recent years, both the entanglement and Shannon Entropy in helium and helium-like ions have also accelerated a great research attention [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…With a pair-correlated wave function approach, it has been shown that through the transition from non-interacting case (BEC-BEC, g B = g AB = 0) to the CP limit (g B = 0 and g AB → ∞), the impurity particle A tends to localize in the edges of the majority species B, when N B = 2, 3 atoms [182]. Then, it has been shown that one can force the impurity particle to again localize in the center of the trap for more massive impurities when N B = 2 to 4 atoms [183] (for the 3+1 system see also appendix in [174]). The limit when g B → ∞ has been studied in [184], showing that when also g AB → ∞ the particles cannot exchange their initial ordering, while when g AB is large but not infinity, the system maps into the spin chain Hamiltonian.…”
Section: H Mixtures With Several Atomsmentioning
confidence: 99%
“…The motion of the centre of mass does not depend on the interaction which influences only the motion of the remaining degrees of freedom. The two-body problem [11] is an example but the separation can also be done for larger number of particles [12][13][14]26,27] at the cost of using more sophisticated methods of describing the relative motion [15,22]. In practice, the mentioned transformation of variables is difficult to perform straightforwardly, however it is a standard tool in a theoretical analysis of few-body problems [30][31][32].…”
Section: The Centre-of-mass Framementioning
confidence: 99%